Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
Executive Director Leroy Cordova speaking to everyone at the dinner; 4 tables of attendees